Synthesis and Biological Evaluation of 3'-C-Ethynyl and 3'-C-(1,4-disubstituted-1,2,3-triazolo) Double-Headed Pyranonucleosides - Kiritsis, Christos; Manta, Stella; Papasotiriou, Ioannis; Coutouli-Argyropoulou, Evdoxia; Trakossas, Sakellarios; Balzarini, Jan; Komiotis, Dimitri (Medicinal Chemistry, 2012)
A novel series of 3'-C-ethynyl and 3'-C-(1,4-disubstituted-1,2,3-triazolo) double-headed pyranonucleosides has been designed and synthesized. Reaction of 3-keto glucoside 1 with ethynyl magnesium bromide gave the desired precursor 3-C-ethynyl-1,2:5,6-di-O-isopropylidene-α-D-allofuranose (2). Hydrolysis followed by acetylation led to the 1,2,4,6-tetra-O-acetyl-3-C-ethynyl-β-D-allopyranose (3). Compound 3 was condensed with silylated 5-fluorouracil, uracil, thymine, N4-benzoylcytosine and N6-benzoyladenine, respectively and deacetylated to afford the target 1-(3'-C-ethynyl-β-D-allopyranosyl)nucleosides 5a-c,f,g. Copper-Catalyzed Azide-Alkyne Cycloaddition (CuAAC) reaction was utilized to couple the 3'-C-ethynyl pyranonucleoside derivatives with azidoethyl adenine, 5-fluorouracil and thymine, respectively to afford novel triazole double-headed nucleoside analogs 8a-h. 3'-C-Ethynyl pyranonucleosides and the new double-headed analogues were evaluated for their antiviral and cytostatic activities. Although none of the compounds showed pronounced cytostatic activity and were devoid of a significant antiviral potential, the double-headed nucleoside derivatives 8a, 8c and 8e showed a moderate cytostatic activity against human cervix carcinoma HeLa cells which may be the basis for the synthesis of analogous derivatives with improved cytostatic potential.
Keywords: triazole